Integrating Weg’s Business Units: How to Generate Positive Externalities Between Business Units of a Global Company in the Process of Internationalization? - Mayer, Beatrice Zanellato; Stuart, Leonardo Carneiro; Martignago, Graciella (Internext, 2022)
Objective: This teaching case describes the trajectory of internationalization of a Brazilian manufacturer of electric motors: WEG. The study proposes to reach the following objectives: (a) understand the company’s process of internationalization from the perspective of international business theories; (b) analyze why the path of internationalization trailed by WEG Automation business unit occurred sequentially to that of WEG Motors; and, (c) reveal if the network of WEG Motors generated positive externalities to the internationalization of WEG Automation. Method: A real case gives the foundation for a teaching case built over primary and secondary data. Primary data was obtained through semi structured interviews with the director and managers of WEG Automation, carried during late 2016. Interviews were transcribed and jointly used with secondary data, acquired from institutional information available at WEG’s website and documents. Moreover, interviewers performed direct observations during long visits to the company. Relevance/originality: Examining the actions of a firm’s internationalization process is valuable in the context of emerging multinational companies, particularly when considering different units feed on internal and external competences during the process, corroborating aspects of the behavioral approach of the Uppsala Models. Theoretical / Methodological Contributions: Applying the theoretical lenses of International Business, such as the Network and Uppsala Models to explain the actions of a Global firm’s internationalization process and, more specifically, to compare the processes of two of its business units – WMO (motors) and WAU (automation). Social / management contributions: This teaching case is recommended for both undergraduate and post-graduate courses in the Administration, Foreign Trade, and International Management fields, for discussions in themes such as: Internationalization of firms, International Business, Internationalization Theories, and Emerging Markets. Using the case helps improving students’ analytical competences regarding the reality of an emerging market firm that becomes a global player.